Superando barreiras à integração da cadeia de suprimentos via método multicritério de apoio à decisão - Aguiar, Fábio Henrique Lima (2021)
Supply Chain Integration plays an important role of influencing the supply chain overall performance. Business competition is taking place between supply chains instead of between companies individually. Academics and practitioners acknowledge the existing barriers, as well as the enablers to establish Supply Chain Integration. However, true collaboration is not found frequently, and few studies of integration have deeply investigated the reasons for such difficulty. Furthermore, the articles do not explore the partners' differences in perspectives and priorities with regard to integration needs, nor the specific solutions to overcome barriers. This study aims, firstly, to debug supply chain integration barriers, prioritizing the most important ones; second, to identify specific, more practical and more feasible solutions from an integration implementation point of view; and, thirdly, to confront the perspective of different partners (suppliers and the focal company) on barriers and solutions. A qualitative approach was used to identify and prioritize specific solutions for supply chain integration, using the Delphi method, and a quantitative approach to prioritize barriers to integration and weigh the impact of each solution against each critical considered barrier, through the HFLTS method (Hesitant Fuzzy Linguistic Terms Set). The results showed that there are two types of solutions for integration, here called critical specific solutions (which strongly affect a specific barrier) and broadband solutions (which moderately affect several barriers), and that there are differences in perspective between focal company and suppliers regarding the criticality and priority of implementation of these solutions. If the perspectives of different partners are not considered when implementing solutions, individual needs can become misaligned in execution time and priorities, compromising the effectiveness of collaboration. The study differs from others by its originality in considering and analyzing two integration perspectives simultaneously, for presenting a list of specific and concrete solutions to achieve integration (instead of more general guidelines, existing in the literature) and for providing clear guidelines for professionals related to the priorities for implementing the solutions.